MINDFULNESS MEDITATION: FORMAL PRACTICES FOR REDUCING STUDENT STRESS (PRÁXIS EM SAÚDE, 2025)
Stress is a common condition among many university students, and psychotherapy is an option to understand and mitigate it; however, many Brazilian universities face difficulties in offering such services. A viable and widely recommended alternative for reducing stress among university students is the adoption of mindfulness meditation practices, whose effectiveness in decreasing stress and managing emotional and behavioral symptoms has been proven, including in online program formats. This study, through an ongoing narrative literature review, aimed to present some of the formal mindfulness practices that can be implemented online by university students, as well as the effects of these practices on stress reduction and the promotion of mental health in this population. Partial results indicate a variety of strategies that are accessible and adaptable to the virtual environment, including sitting meditation, breathing meditation, and body scan, with the programs being mainly derived from Mindfulness-Based Stress Reduction and Mindfulness-Based Cognitive Therapy. The partial findings suggest that, even outside of face-to-face contexts and with limited initial guidance, students can develop an autonomous and sustainable practice with the support of online resources.
Keywords: Meditation; University Students; Stress; Formal Mindfulness Practices